Regulating water extraction in a river basin with upstream-downstream communities - Mette Kildegaard Graversen (University of Copenhagen, Department of Food and Resource Economics (IFRO), 2011)
This paper proposes a tax mechanism modelled for water extraction in a river system with upstream and downstream farmers. The tax mechanism is based on the regulator's own estimation of aggregate extraction and for that reason the tax addresses the problem of asymmetric information. It is demonstrated that the tax mechanism ensures approximately correct marginal extraction incentives for the individual farmer. Consequently, it is concluded that the tax mechanism proposed here has a practical application.
Keywords: 330; Water extraction; River system; Tax mechanism; Upstream-downstream users